UJI ANTAGONISME Fusarium oxysporum f.sp. passiflora TIPE MUTASIAN TERHADAP Fusarium oxysporum f.sp. passiflora TIPE LIAR DI LABORATORIUM - Lisnawita Lisnawita; Muklis Adi Putra; Hasanuddin Hasanuddin; Lisnawita Lisnawita (Universitas Sumatera Utara, 2013)
Antagonism test between mutated type of Fusarium oxysporum f.sp passiflora against wild type ofFusarium oxysporum f.sp passiflora in laboratory. This research aims to determine antagonismpotentiality from mutated type of F. oxysporum f.sp. passiflora against wild type of F. oxysporumf.sp. passiflora. The research was conducted at Plant Disease Laboratory, AgroecotechnologyProgram Study, Faculty of Agriculture University of Sumatera Utara, Medan from September toNovember 2012. The research was done by using Completely Randomized Design (CRD) NonFactorial with ten treatments and three replications. The result showed that the highest percentageof inhibiting zones contained in 60 minutes ulta violet (UV) irradiated isolate (M9) at 54.45% andthe lowest were in without UV irradiated isolate (M0) at 39.27%, highest extensive growth ofmycelium from wild F. oxysporum was founded at 60 minutes UV irradiated isolate (M9) at 35.05cm2 and the lowest were 12 minutes UV irradiated (M5) at 25.36 cm2. The highest colony diameterwas founded at 60 minutes UV irradiated isolate (M9) at 5.53 cm and the lowest were 12 minutesUV irradiated (M5) at 4.67 cm.Keywords : Fusarium oxysporum f.sp passiflora, antagonism, UV irradiation